Stable and Transformed Motives in the Yakut Olonkho (Northern Epic Tradition) - Koryakina, Antonina Fedorovna; Zhirkova, Evgenia Egorovna (Journal of History Culture and Art Research, 2018)
In Yakut folklore studies, depending on the territory of existence, there are three traditions of narrative: Central, Viluysk and Northern. In modern science, the phenomenon of stable regional features of the plot motives of the Yakut olonkho is still relevant. The article is based on the comparative-typological study of the Northern olonkho on the material of the legends of the four Northern districts (ulus) in order to identify stable northern regional traditions in motives and establish ways and means for their transformation. The theoretical substantiation of the research is the works of folklorists on the stability of the main plot of the oral tradition (A. Lord), about a single type (with possible internal subdivisions into subtypes) of epic singers of each ethnic tradition (B.N. Putilov), about the originally creative epic beginning (Parry and A. Lord), on the influence of the improvisation of the narrator on the geographical location of folklore (V.M. Zhirmunsky), on the motive as a plot-forming element (B.N. Putilov), on the uniformity of constructing the main constituent element of the works of the oral people creativity V.Ya. Propp), regional and local traditions of the Yakut narrative (V.V. Illarionov, T.V. Illarionova, A.A. Kuzmina, G.S. Popova, G.A. Sosina), the features of the Evenk and Evenki epos (A.A. Burykin), about typical places for the epic of the Turkic-Mongolian peoples of Siberia (E.N. Kuzmina). As a result of the study, stable epic motives of the Northern olonkho are determined, some conclusions of Yakut researchers are expanded on its features, the position about the existence of a stable northern tradition is confirmed, the assumption is suggested of the mutual influence of the traditions of the Northern olonkho and the epic traditions of the Even and Evenki eposes.